TRANSFORMASI PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL: STUDI KASUS DI SMP N 1 JEPON - Uzlifatil Jannah; Ahmad Syaifulloh; Siti Nurkayati (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This research aims to examine the transformation of Islamic Religious Education (PAI) in the digital era, using a case study at SMP Negeri 1 Jepon. This transformation is crucial because advances in information and communication technology have brought about significant changes in the learning process, including in Islamic Religious Education (PAI). A qualitative approach was used in this study, with data collected through observation, interviews, and documentation. The results indicate that the use of digital media, such as e-learning platforms, learning applications, and social media, can improve the effectiveness of Islamic Religious Education (PAI) learning, both in terms of material distribution and teacher-student interaction. Factors supporting this transformation include the availability of technological facilities, teachers' ability to utilize digital media, and students' desire to learn. However, the study also found several obstacles, such as limited internet access, differences in students' digital literacy, and the need for intensive teacher mentoring. Overall, the PAI transformation undertaken at SMP Negeri 1 Jepon demonstrates that digitalization helps make learning more interactive, contextual, and relevant to the needs of the digital generation.